Impact of Some of the Important Insecticides on Final Seed Yield of Bell Pepper (Capsicum annuum L.) - Meena, Har Lal; Rana, Kiran; Mehta, D. K.; Lal, Manohar; Kanwar, Rajesh (International Journal of Bio-resource and Stress Management, 2018)
The present studies were carried out at Department of Seed Science and Technology, Dr. Y. S. Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh, India during kharif season 2013 to see the impact of some of the important insecticides on final seed yield of bell pepper (Capsicum annuum L.) cultivar Solan Bharpur. The treatments comprised of seed application of imidacloprid (Gaucho 600FS) and thiamethoxam (Cruiser 70WS), soil application of neem cake@ 2 q acre-1 and Carbofuran @ 6 kg acre-1 and foliar spray of imidacloprid (Confidor 200 SL), thiamethoxam (Actara 25 WS), indoxacarb @ 0.5 ml l-1, NSKE (neem seed kernel extract) 5%, neem formulation @ 2.5 ml l-1 and control condition (without any spray). The observations included number of seeds fruit-1, thousand seed weight (g), seed yield plant-1 (g), seed yield plot-1 (g) and seed yield ha-1 (kg) and also the benefit: cost ratio was worked out. The result revealed that treatment combination viz., seed treatment and foliar spray with thiamethoxam recorded significantly higher number of seeds fruits-1 (190.66), 1000 seed weight (5.58 g), seed yield plant-1 (18.91 g), seed yield plot-1 (385.81 g), seed yield ha-1 (714.46 kg) and benefit: cost ratio (4.52:1). Thus thiamethoxam, both as seed treatment and foliar spray may be recommended for insect free higher seed yields of bell pepper.